2010
DOI: 10.1093/acprof:oso/9780199603404.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

The Philosophical Foundations of Extraterritorial Punishment

Abstract: 187 pages. 9.25x6.25x0.50 inches. In Stock. 9 dec 2010. The principle of extraterritorial punishment, which enables national courts to exert jurisdiction over crimes committed abroad by nationals of Lese bok The Philosophical Foundations of Extraterritorial. The principle of extraterritorial punishment, which enables national courts to exert jurisdiction over crimes committed abroad by nationals of other states, has. Ireland-Piper, Danielle-Abuse of Process in Cross-Border Cases. Get this from a library! The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Chehtman also assessed the notion of extra jurisdictional legislation where he suggested that a state's power to punish an offender is only justified where the collective interests of individuals in that state have an interest in a system of laws being in force and enforced. He argues that some assertions of extraterritoriality may not be justified by a sufficient collective interest by the domestic population of the asserting state [50].…”
Section: Application Of Extraterritorial Jurisdiction By States Reflementioning
confidence: 99%
“…Chehtman also assessed the notion of extra jurisdictional legislation where he suggested that a state's power to punish an offender is only justified where the collective interests of individuals in that state have an interest in a system of laws being in force and enforced. He argues that some assertions of extraterritoriality may not be justified by a sufficient collective interest by the domestic population of the asserting state [50].…”
Section: Application Of Extraterritorial Jurisdiction By States Reflementioning
confidence: 99%
“…These crimes can be punished by international tribunals (like the International Criminal Court) or by individual states through the legal construct of universal jurisdiction, including over the objection of the state where the atrocities took place. Most theories, from initial attempts by Luban (), May (), and Altman and Wellman () to more recent work, tend to focus on the gravity of the crimes as a basis for what some of them call an international jurisdiction that encompasses both trials by international tribunals and by all states (Lee, , p. 18; Chehtman, ). Song's () account of universal jurisdiction rejects the attempt to match international crimes with gravity but sees it as an attempt by states to address gaps in the ability of states to enforce criminal law.…”
Section: Engagement With International Law: Two Modalitiesmentioning
confidence: 99%
“…For example, Chehtman accepts that individuals within a given state have a collective interest in the security of their state being protected. 104 He argues that 'the fact that a given state can abuse a right it has is hardly a conclusive argument against it initially holding that right. '…”
Section: What Is An Example Of Protective Principle Jurisdiction?mentioning
confidence: 99%